PERMANENT-MAGNET ROTARY MOTORS - Sakhanov, I; Veselkov, A; Ilin, Aleksandr (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
Different types of traction motors (DC, asynchronous, valve with excitation from permanent magnets) are compared. It is demonstrated that a valve motor with excitation from permanent magnets is the most suitable for using in electric vehicles and electric buses.